Optimal Location of Wells for Storage and Recovery of Surplus Desalinated Water in Coastal Aquifers. Issue 5 (16th December 2019) - Triki, Chefi; Zekri, Slim; Al‐Maktoumi, Ali; Bazargan‐Lari, Mohammad R.
Abstract: Storage of water in aquifers using injection wells is an efficient way for utilizing excess desalinated water in arid regions. In this investigation we estimate the benefits of optimally recharging seasonal surplus desalinated water into a strategic coastal aquifer already benefitting from natural recharge of flash‐floods water by a recharge dam. Since, usually the buyers of desalinated water commit to purchase surplus desalinated water under take‐or‐pay contracts, any attempt in utilizing the paid water is beneficial. Coastal cities are observing an increased urbanization leaving limited space for aquifer recharge infrastructure. In order to determine the optimal location of wells and maximize the use of surplus desalinated water available in winter period, a decision tool combining a numerical groundwater flow simulation model (MODFLOW) with an optimization model is developed. The results of this study show that increasing the number of wells from the existing 45 wells to 173 would allow storing 31.4 million cubic meter per year of excess desalinated water into the aquifer that can be used during later during summer months. The net benefit would reach US$55 million/year while the cost of drilling the new wells is US$5.11 million. Abstract : Article impact statement : Optimization techniques for the location of wells for injection, storage and recovery of surplus desalinated water in coastal aquifers.